Asymmetrical Neighborhood of the Empire and a Small Nation in the Far North: The Image of the Russian “Otherness” and Russian-Swedish/Norwegian Relations in the 19th — Early 20th Centuries - Konstantin S. Zaikov; Oksana V. Zaretskaya (Арктика и Север)
The work examines the features of relations between the Russian Empire and Sweden and Norway in the context of the asymmetric proximity of the 19th - early 20th centuries. The authors have analyzed and identified specific features characteristic of the asymmetrical neighborhood of the empire and a small nation, as well as factors in the formation of ideas about the “Russian threat” to Sweden and Norway during this period and have traced the stages and dynamics of the transformation of these ideas in the Scandinavian countries. Russian-Norwegian and Russian-Swedish relations go back several centuries of asymmetrical proximity, contacts and conflicts, which, of course, influenced the formation of images of the “eastern neighbor”. The Swedes and Norwegians’ fears and expectations, based on perceptions of themselves, about their collective “Self”, contributed to the formation of images of the Russian “Otherness”, the attitude towards which was ambiguous and primarily depended on internal preconditions. Therefore, a detailed study of the transformation of images of Russia in Norway and Sweden allows us to take a new look at the history of relations between these countries, as well as to identify the domestic and foreign policy interests of Norwegian and Swedish societies associated with certain images of Russia.